KEMAMPUAN MAHASISWA DALAM PENDEFINISIAN MASALAH PADA PEMBELAJARAN BERBASIS RISET - Trisna Amelia (UIR Press, 2020)
Biology Seminar is a course in the Biology Education Study Program of FKIP UMRAH that requires students to have the ability to apply scientific attitudes, perform scientific writing, and undertake scientific publications on a small scale. One of the learning strategies that can drive the achievement of learning outcomes is Research-Based Learning. One type of research-based learning is that which facilitates students doing small-scale research. Small-scale research is conducted by students applying scientific methods and train students to have a scientific attitude. This paper was derived based on descriptive research conducted to reveal how the defining problem skill formed by the research-based learning process. The instrument used was a questionnaire and documentations of 44 students brainstorming the topic. The assessment is given based on several indicators, namely the ability; explain the source of the problem, explain the problem phenomenon, identify more than one problem topic, choose the focus of the problem, construct the problem formulation, and find supporting references. From the study, it was known that students defining problem skills were in the high category.